Spectral Investigation of Ligand-Metal Composition Using Dye Indicators - N. Modi, Ashvin; Farasram, P.L.; Desai, C.M. (Asian Journal of Chemistry, 2010)
The reagents β-arylamino crotono anilides were prepared and the dyeindicator method was used to investigate the composition of number ofcomplexes between ligand and metal ions and hence ML and ML2 typecomplexes of zinc and cadmium were prepared and characterised.